Do small and medium companies in Malaysia prioritise sustainable development goals? - Sarma Aralas (Penerbit UMT, 2021)
Sustainable development goals of the 2030 agenda adopted by the United Nation are intended as a shared blueprint for developing and developed countries to achieve sustainable development that brings peace and prosperity to all nations now and into the future. The 17 sustainable development goals include targeted objectives of achieving zero poverty, zero hunger, good health and well-being, quality education, gender equality, and clean water and sanitation. This paper presents the results of a survey of 67 small and medium sized Malaysian companies on the progress they are making towards achieving the goals of sustainable development. Our findings show that companies are making some progress on the desired outcome of attaining the 17 sustainable development goals. However, greater effort is required for sufficient progress to achieve the goals. Such effort implies the requisite to prioritize sustainable development goals in the firm’s business actions and practices. There is a need to increase awareness of the importance of the sustainable development goals to achieve the 2030 agenda as set by the global community.